(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article comprehended specificity of the phenomenon of fear in the A.P.Dovzhenko’s movie-stories of the war. Particular attention is focused on ways to express this emotional modus on different levels of the text organization of the creator’s prose.